LITERARY READING: HÖLDERLIN THROUGH HEIDEGGER THROUGH DE MAN - Pelmas, Sarah (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1993)
This essay examines how the stakes of literary theory can be understood within the activity of reading. Through Paul de Man's reading of Martin Heidegger's reading of Friedrich Hölderlin, this essay analyzes the way that Heidegger uses Hölderlin's poetic language, examples, and etymology to elaborate his own thought — thought which ultimately demands to be read. By understanding de Man's response to Heidegger's thinking, we can see how readings must respond to thought precisely because language requires the reader to recover the moments language is always documenting as already lost.